Contribution of Precision Livestock Farming Systems to the Improvement of Welfare Status and Productivity of Dairy Animals - Simitzis, Panagiotis E; Tzanidakis, Christos; Tzamaloukas, Ouranios; Sossidou, Evangelia (My University, 2022)
Although the effects of human–dairy cattle interaction have been extensively examined, data concerning small ruminants are scarce. The present review article aims at highlighting the effects of management practices on the productivity, physiology and behaviour of dairy animals. In general, aversive handling is associated with a milk yield reduction and welfare impairment. Precision livestock farming systems have therefore been applied and have rapidly changed the management process with the introduction of technological and computer innovations that contribute to the minimization of animal disturbances, the promotion of good practices and the maintenance of cattle’s welfare status and milk production and farms’ sustainability and competitiveness at high levels. However, although dairy farmers acknowledge the advantages deriving from the application of precision livestock farming advancements, a reluctance concerning their regular application to small ruminants is observed, due to economic and cultural constraints and poor technological infrastructures. As a result, targeted intervention training programmes are also necessary in order to improve the efficacy and efficiency of handling, especially of small ruminants.
Keywords: Small ruminants; Aversive handling; Precision livestock farming systems; Animal welfare; Milk production